The Legal Strength of SK KINAG in Contemporary Landreform Land Ownership - Nurfadilah Cintiarossati; Amad Sudiro (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
This study examines the legal force of land ownership derived from the land reform program through the Decree of the Head of the Agrarian Inspection Office (SK KINAG) within the context of contemporary land law. Land reform in Indonesia represents a form of state intervention aimed at restructuring land tenure in a fair manner through redistribution mechanisms. SK KINAG functions as an administrative instrument that legitimizes the determination of land subjects and objects in the implementation of such policies. However, the development of the modern land law system, which emphasizes land registration and certification, has affected the position of SK KINAG within the system of proof of land rights. This research employs a qualitative method with conceptual and statutory approaches, supported by secondary data in the form of legislation, books, and scholarly journals. The analysis is conducted descriptively to assess the current legal validity of SK KINAG. The results indicate that SK KINAG holds administrative and historical value as an initial basis for land control; however, it does not provide strong legal certainty comparable to land title certificates. Therefore, conversion through land registration mechanisms is necessary to obtain more definite legal recognition and effective protection within the modern land law system.